HUBUNGAN TEKNIK PERLEKATAN MENYUSUI DENGAN DURASI SESI PEMBERIAN ASI IBU POSTPARTUM PRIMIPARA - Dika Lintang Isabella; Sumy Dwi Antono; Lumastari Ajeng Wijayanti; Ira Titisari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Proper breastfeeding attachment is one of the key factors influencing successful breastfeeding, particularly among primiparous postpartum mothers who have no previous breastfeeding experience. Incorrect attachment may hinder effective breast milk transfer, cause maternal discomfort, and affect the duration of each breastfeeding session. This study aimed to analyze the relationship between breastfeeding attachment technique and the duration of each breastfeeding session among primiparous postpartum mothers in the working area of Sukorame Public Health Center, Kediri City. This quantitative study employed a longitudinal analytical correlational design. A total of 36 primiparous postpartum mothers were selected using probability sampling. Data were collected through direct observation using the LATCH Score instrument and recording the duration of breastfeeding during two measurement periods. The data were analyzed using the Spearman Rank correlation test with a significance level of α = 0.05. The results showed improvements in breastfeeding attachment technique and increased breastfeeding duration at the second measurement. Spearman Rank analysis revealed a significant relationship between breastfeeding attachment technique and the duration of each breastfeeding session at the first measurement (p = 0.020; r = -0.385) and the second measurement (p = 0.004; r = -0.470). It can be concluded that breastfeeding attachment technique is significantly associated with the duration of each breastfeeding session. Therefore, education and assistance regarding proper breastfeeding attachment techniques should be optimized to support successful breastfeeding among primiparous postpartum mothers. ABSTRAK Teknik perlekatan menyusui merupakan salah satu faktor penting yang memengaruhi keberhasilan pemberian ASI, terutama pada ibu postpartum primipara yang belum memiliki pengalaman menyusui. Perlekatan yang kurang tepat dapat menghambat transfer ASI, menimbulkan ketidaknyamanan pada ibu, serta memengaruhi durasi setiap sesi menyusui. Penelitian ini bertujuan menganalisis hubungan antara teknik perlekatan menyusui dengan durasi setiap sesi pemberian ASI pada ibu postpartum primipara di wilayah kerja Puskesmas Sukorame Kota Kediri. Penelitian menggunakan metode kuantitatif dengan desain korelasi analitik longitudinal. Sampel penelitian berjumlah 36 ibu postpartum primipara yang dipilih menggunakan teknik probability sampling. Data dikumpulkan melalui observasi menggunakan instrumen LATCH Score dan pencatatan durasi menyusui pada dua kali pengukuran, kemudian dianalisis menggunakan uji Spearman Rank dengan tingkat signifikansi α = 0,05. Hasil penelitian menunjukkan adanya perbaikan teknik perlekatan menyusui dan peningkatan durasi menyusui pada pengukuran kedua. Analisis Spearman Rank menunjukkan terdapat hubungan yang bermakna antara teknik perlekatan menyusui dengan durasi setiap sesi pemberian ASI pada pengukuran pertama (p = 0,020; r = -0,385) dan pengukuran kedua (p = 0,004; r = -0,470). Disimpulkan bahwa teknik perlekatan menyusui berhubungan secara signifikan dengan durasi setiap sesi pemberian ASI, sehingga edukasi dan pendampingan mengenai teknik perlekatan yang benar perlu dioptimalkan untuk mendukung keberhasilan menyusui pada ibu postpartum primipara.